A prospective cohort study of enteric pathogens in human immunodeficiency virus-infected Indian children and their relationship with diarrheal recurrence - Dewan, Pooja; Mardi, Dhano; Gomber, Sunil; Saha, Rumpa (International Journal of Contemporary Pediatrics, 2019)
Background: Opportunistic intestinal infections can increase the risk of death 11- fold in Human immunodeficiency virus (HIV) infected children presenting with diarrhea. Understanding the etiology of diarrhea and its predictors can help strategize a targeted approach to reduce child mortality due to diarrhea in this vulnerable group. Authors aim was to compare the enteric pathogens in HIV-infected children with and without acute diarrhea, to assess the association between carriage of enteric pathogens in HIV-infected children and the occurrence of diarrhea within the next 3 months and to ascertain the relationship between enteric pathogens in HIV-infected children with their immunological and nutritional status. Methods: Stool samples were collected from HIV-infected children with acute diarrhea (n=41) and without diarrhea (n=52). All samples were subjected to microscopic examination, modified acid-fast and Trichrome staining, hanging drop examination, and bacterial culture. Serology for Cryptosporidium parvum was determined. Children who had received any antimicrobial therapy within the previous 2 weeks were excluded. Participants were followed up for three months for occurrence of diarrhea. Results: Intestinal pathogens were isolated in 48.8% and 42% of children in the diarrheal and non-diarrheal group respectively. The most common pathogens isolated in the diarrheal and non-diarrheal group were Cryptosporidium parvum and Escherichia coli (29.3% vs. 17.3%). During follow up, 8 children in each group had diarrheal occurrence. The pathogen isolated in subsequent episodes matched with the initial isolate in 3 children in each group. Conclusions: HIV-infected children without diarrhea also harbour enteric pathogens in comparable proportions to symptomatic children, which can predispose them to diarrheal occurrence in future, hence indicating need for assessing the need for preventive screening and prophylactic antibiotic regimens in this vulnerable group.